Effect of Chlorella on hematological parameters and nutrient bioavailability in the diet of rhesus monkeys (Macaca mulatta) - N. V. Gaponov; Al. V. Panchenko; An. V. Panchenko; Yu. P. Chuguev (Ветеринария сегодня)
Chlorella shows a wide spectrum of biological activity, in particular, it exhibits a pronounced antioxidant activity and demonstrates anti-inflammatory, antitumor and antiviral properties. A number of research works have been devoted to studying feed advantages of this unicellular green algae when used in the diets of livestock animals, but the possibility of including different Chlorella species in the diet of primates has not been practically studied. The aim of this work was to assess the possibility of replacing high-protein animal and vegetable feeds with Chlorella, to calculate the digestibility coefficients for the diet nutrients and the effect of algal dry and suspension forms on hematological and serum biochemical parameters in male rhesus monkeys. The data obtained during the experiment indicate that the inclusion of Chlorella in the diet both in the dry form and cell suspension improves nutrient digestibility. Thus, the digestibility of crude protein in the animals receiving algae suspension increased by 4.18% (p < 0.05), that of crude fat – by 4.70% (p < 0.01), crude fiber – by 4.14% (p < 0.05) and crude ash – by 12.32% (p < 0.001). The digestibility coefficients of crude protein in the primates receiving compound feed supplemented with Chlorella powder were higher by 6.83% (p < 0.001), those of crude fiber – by 4.78% (p < 0.05) and crude ash – by 18.93% (p < 0.001) The hematological study results indicate the absence of side effects from long-term Chlorella consumption by primates. The introduction of dry Chlorella into the diet increased blood glucose levels to the upper limit of the control values, while Chlorella suspension did not produce this effect. Thus, Chlorella can be successfully used as a component of a balanced laboratory diet for primates or as a feed additive.